2011
DOI: 10.1128/jcm.05481-11
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Enzooticity of Hepatitis E Virus Genotypes 1 to 4 in the United States

Abstract: Hepatitis E is recognized as a zoonosis, and swine are known reservoirs, but how broadly enzootic its causative agent, hepatitis E virus (HEV), is remains controversial. To determine the prevalence of HEV infection in animals, a serological assay with capability to detect anti-HEV-antibody across a wide variety of animal species was devised. Recombinant antigens comprising truncated capsid proteins generated from HEV-subgenomic constructs that represent all four viral genotypes were used to capture anti-HEV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 62 publications
3
59
0
Order By: Relevance
“…We noticed seroprevalence of 11.76% in moose and no positive samples of 3 European bison. Meanwhile, in the United States where bison meat is increasingly consumed, 4.6% of domesticated bison (Bison bison) were positive for HEV antibodies (Dong et al 2011). Notably, the absence of seropositivity in European bison samples is not significant due to the small sample size, but the results are in line with a report from Poland where HEV antibodies were not found in any of the 68 European bison (Bison bonasus) tested (Larska et al 2015).…”
Section: Discussionsupporting
confidence: 80%
“…We noticed seroprevalence of 11.76% in moose and no positive samples of 3 European bison. Meanwhile, in the United States where bison meat is increasingly consumed, 4.6% of domesticated bison (Bison bison) were positive for HEV antibodies (Dong et al 2011). Notably, the absence of seropositivity in European bison samples is not significant due to the small sample size, but the results are in line with a report from Poland where HEV antibodies were not found in any of the 68 European bison (Bison bonasus) tested (Larska et al 2015).…”
Section: Discussionsupporting
confidence: 80%
“…2). HEV-3 is prevalent among swine worldwide (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86) as well as in other mammals, including deer and mongooses (83,(87)(88)(89), though little is known about the sylvatic circulation of HEV.…”
Section: Epidemiologic Patterns Of Hepatitis E Virus Infectionmentioning
confidence: 99%
“…It has been recognized recently that patients who have had solid-organ or bone marrow transplants are at risk of developing chronic HEV infection if they are infected after their transplant while being treated with immunosuppressive drugs to prevent rejection of the allograft (76,(254)(255)(256)(257). Kamar and colleagues evaluated the factors associated with chronic hepatitis in 85 patients with HEV infection from 17 transplant centers in Europe and North America (275) (Fig.…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%
“…In the United States seropositivity reached 41% (12), 90% in New Zealand (13), 100% in Mexico (14) and 98% in Spain (15). Studies in Latin America have reported the circulation of HEV in pigs in Argentina (16), Brazil (17), Chile (18), Costa Rica (19) and Mexico (14).…”
Section: Introductionmentioning
confidence: 99%